2020
DOI: 10.3390/ijms21010368
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Adaptation to Sulfur of Hyperthermophilic Palaeococcus pacificus DY20341T from Deep-Sea Hydrothermal Sediments

Abstract: The hyperthermo-piezophilic archaeon Palaeococcus pacificus DY20341T, isolated from East Pacific hydrothermal sediments, can utilize elemental sulfur as a terminal acceptor to simulate growth. To gain insight into sulfur metabolism, we performed a genomic and transcriptional analysis of Pa. pacificus DY20341T with/without elemental sulfur as an electron acceptor. In the 2001 protein-coding sequences of the genome, transcriptomic analysis showed that 108 genes increased (by up to 75.1 fold) and 336 genes decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Some strains, such as Pyrococcus kukulkanii or Palaeococcus ferrophilus, require sulfur or Fe (II) in the culture medium to grow, and some others can grow via carboxydotrophy. Thermococcales strains require high temperatures to grow; some of them also can survive for a long time in cold conditions, such as hydrothermal sediments and then quickly respond to the high temperature and energy supply by complex organic matter or elemental sulfur (Mora et al 2014;Zeng et al 2020). Piezophilic features are also widespread in this order (Dalmasso et al 2016;Zeng et al 2009) and some strains tolerate high doses of gamma radiation (Jolivet et al 2004).…”
Section: Archaea-euryarchaeotamentioning
confidence: 99%
“…Some strains, such as Pyrococcus kukulkanii or Palaeococcus ferrophilus, require sulfur or Fe (II) in the culture medium to grow, and some others can grow via carboxydotrophy. Thermococcales strains require high temperatures to grow; some of them also can survive for a long time in cold conditions, such as hydrothermal sediments and then quickly respond to the high temperature and energy supply by complex organic matter or elemental sulfur (Mora et al 2014;Zeng et al 2020). Piezophilic features are also widespread in this order (Dalmasso et al 2016;Zeng et al 2009) and some strains tolerate high doses of gamma radiation (Jolivet et al 2004).…”
Section: Archaea-euryarchaeotamentioning
confidence: 99%
“…Deep-sea hydrothermal vent is one of the most extreme environments on earth and provides unique and diverse habitats for various microorganisms (Zeng et al, 2020). However, the sharp physical and chemical gradients across the vent chimneys and their surroundings impose great challenges to bacterial survival (Sievert et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that polysaccharides recycled at the ocean bottom can remain there for a long time and are important carbon sources for the hadal microbiota (Nunoura et al, 2015;Luo et al, 2017). Evidence that protein degradation provides important carbon sources, indicated by the abundance of dipeptide and oligopeptide transporters, has been also documented in previous studies on deep-sea microbes (Zhang et al, 2015;Zeng et al, 2020). Excepting the Sulfitobacter sp.…”
Section: A L C a N I V O R A X A L I I D O N G I A A L T E R O M O N A S A N A E R O H A L O S P H A E R A B U R K H O L D E R I A C A N mentioning
confidence: 82%